Implications of Halal Certificates for Micro, Small and Medium Enterprises - Mudhofar, Muhammad; Wibisono, Yusuf; Samsuranto, Samsuranto (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Halal certification for micro, small, and medium enterprises (MSMEs) is a form of government recognition that guarantees the halal status of a product complied with by business actors. The urgency of this research lies in the increasing importance of halal certification as a standard of consumer trust and a driver of competitiveness in the halal industry. This study aims to analyze the implications of halal certification on MSMEs in Lumajang Regency. The research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. Primary data were obtained from respondents’ interviews, while secondary data came from relevant documents. Data analysis was conducted in three stages: data reduction, data presentation, and conclusion drawing. The findings show that halal certification has significant implications for MSMEs, particularly in enhancing product credibility and business sustainability. The policy provides economic benefits by expanding market opportunities, optimizing the captive market, and increasing producer turnover. Moreover, halal certification positively contributes to regional economic development by opening employment opportunities for auditors and facilitators of halal product processes. These results emphasize that the implementation of halal certification is not only a compliance requirement strategic instrument for strengthening the halal business ecosystem in Lumajang Regency.